Jatrorrhizine: A Review of Sources, Pharmacology, Pharmacokinetics and Toxicity - Furong Zhong; Furong Zhong; Yang Chen; Yang Chen; Jia Chen; Jia Chen; Hailang Liao; Hailang Liao; Yirou Li; Yirou Li; Yuntong Ma; Yuntong Ma (Frontiers Media S.A., 2022)
Jatrorrhizine, an isoquinoline alkaloid, is a bioactive metabolite in common medicinal plants, such as Berberis vernae Schneid., Tinospora sagittata (Oliv.) Gagnep. and Coptis chinensis Franch. These plants have been used for centuries in traditional medicine for their wide-ranging pharmacological properties. This review emphasizes the latest and comprehensive information on the sources, pharmacology, pharmacokinetics and toxicity of jatrorrhizine. Studies on this alkaloid were collected from scientific internet databases, including the Web of Science, PubMed, ScienceDirect, Google Scholar, Elsevier, Springer, Wiley Online Library and Europe PMC and CNKI, using a combination of keywords involving "jatrorrhizine", "sources", "pharmacology," "pharmacokinetics," and "toxicology". Jatrorrhizine exhibits anti-diabetic, antimicrobial, antiprotozoal, anticancer, anti-obesity and hypolipidemic properties, along with central nervous system activities and other beneficial activity. Studies of jatrorrhizine have laid the foundation for its application to the treatment of various diseases, but some issues still exist. Further investigations might emphasize 1) specific curative mechanisms of jatrorrhizine and clinical utility, 2) application prospect in the treatment of metabolic disorders, 3) comprehensive investigations of the toxicity mechanisms and 4) interactions of jatrorrhizine with other pharmaceuticals and development of derivatives.